Education for a sustainable future at the University: The challenge of teacher training - Vilches, Amparo; Gil Pérez, Daniel (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
We analyze in this paper the importance of incorporating Sustainability in Higher Education Curricula as an essential component of future professionals’ training. We show some advances in university teaching, management and research, refer to the main difficulties encountered and suggest ways of facing them. Our study is mainly centered in teachers’ training of different levels, through their immersion in the culture of sustainability, to enable them to contribute to citizens’ preparation to participate in founded decision-making about the socio-environmental problems currently faced by humanity.